2013
DOI: 10.1007/s13277-013-1450-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations at microRNA and processing genes and risk of oral cancer

Abstract: Genetic variations at microRNA and microRNA processing genes are known to confer risk of cancer in different populations. Here, we studied variations at eight microRNA (miRNA) and four miRNA processing genes in 452 controls and 451 oral cancer patients by TaqMan genotyping assays. Variant allele-containing genotypes at mir-196a2 and variant allele homozygous genotype at Ran increased the risk of cancer significantly [adjusted odds ratio (OR) (95% confidence interval (CI)) = 1.3 (1-1.7) and 2.3 (1.1-4.6), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…So, it needs to be investigated whether these two SNPs are in LD. In our recent study on cancer patients, we got similar results for Gemin3 and mir-34b [13]. It is interesting to study how these two polymorphisms alter risk of both oral precancer and cancer.…”
Section: Discussionsupporting
confidence: 67%
“…So, it needs to be investigated whether these two SNPs are in LD. In our recent study on cancer patients, we got similar results for Gemin3 and mir-34b [13]. It is interesting to study how these two polymorphisms alter risk of both oral precancer and cancer.…”
Section: Discussionsupporting
confidence: 67%
“…Following the study selection criteria, 107 studies were excluded in the first step of title and duplicate screening step, and 16 studies were subsequently excluded from our research due to various deficiencies(3 were reviews, 5 were not on the research polymorphism locus, and 8 were focused on cell line and others). In total, 11 eligible articles were selected with adequate data 27 33 34 35 36 37 38 39 40 41 42 , including seven studies on microRNA-146a rs2910164 G > C 27 34 35 36 37 38 40 , five studies on microRNA-196a2 rs11614913 C > T 33 34 35 41 42 , three publications on microRNA-149 rs2292832 C > T 34 35 39 , and two studies on microRNA-499 rs3746444 A > G 34 35 , respectively. Four studies involved Caucasian populations 27 33 34 37 , and seven studies involved Asian populations 35 36 38 39 40 41 42 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 11 eligible articles were selected with adequate data 27 33 34 35 36 37 38 39 40 41 42 , including seven studies on microRNA-146a rs2910164 G > C 27 34 35 36 37 38 40 , five studies on microRNA-196a2 rs11614913 C > T 33 34 35 41 42 , three publications on microRNA-149 rs2292832 C > T 34 35 39 , and two studies on microRNA-499 rs3746444 A > G 34 35 , respectively. Four studies involved Caucasian populations 27 33 34 37 , and seven studies involved Asian populations 35 36 38 39 40 41 42 . Regarding the genotyping method, eight studies used the Applied Biosystems 27 33 35 36 39 40 41 42 , two studies adopted polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) 34 35 , one study used PCR with two-pair primers method 37 and another was conducted with the MassARRAY iPLEX platform 38 .…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that miRNAs could have played important roles in tumor development, diagnosis and prognosis (5). Studies have demonstrated that the single-nucleotide polymorphisms (SNPs) or mutations in miRNA-coding genes functionally affected the expression and biogenesis of mature miRNAs and their target genes, consequently contributing to cancer susceptibility (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%